Perlindungan Hukum Pejabat Pembuat Akta Tanah Atas Ketidaksesuaian Hasil Pengecekan Sertipikat Oleh Badan Pertanahan Nasional - Binti, Sheila Binti Devina (UNES Law Review, 2023)
The results of checking the certificate by the National Land Agency stating that the certificate is the same as the physical certificate issued by the National Land Agency is a mandatory requirement before the Land Deed Making Official makes a Deed for the transfer of land rights. But what about the results of the check which turns out to be inconsistent with the original condition of the certificate and results in the transfer of rights not being able to continue? Based on this background, the researcher used normative juridical research methods, in this case Land Deed Making Officials do not yet have clear enough legal protection for their profession, on the other hand, in carrying out their mandate as Public Officials, especially if there are cases or disputes related to the transfer of land rights.